Pengaruh Model Pembelajaran Student Teams Achievement Division (STAD) terhadap Hasil Belajar Ditinjau dari Minat Siswa dalam Pembelajaran PAI di UPTD SDN 02 Taram - Nuur Aini; Siska Yulia Rahmi; Yulia Rahman; M. Arif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research was motivated by the problem of students who were less active in asking and answering questions and did not pay attention to the teacher when explaining the material. The aim of this research is to determine the effect of the STAD learning model on learning outcomes in terms of students' high interest, medium interest and low interest. The sample in this study was 42 class V students of UPTD SDN 02 Taram, using a saturated sampling technique. This research design uses quasi-experiment, because it involves 2 groups, namely the experimental group and the control group. Data collection techniques use questionnaires and test questions. Based on the results of research and data analysis, the t test calculation was found to be influential or Ha was accepted. So, from the results of the t test it is known that students' high interest is obtained tcount = 1.075; ttable for the 5% significance level is 2.446. So, tcount < ttable. This means that Ha is influenced or accepted. Medium interest obtained tcount = 0.742; ttable for the 5% significance level is 2.048. So, tcount < ttable. This means that Ha is influenced or accepted. Meanwhile, low interest obtained tcount = 1.526; ttable for the 5% significance level is 4.302. So, tcount < ttable. This means that Ha is influenced or accepted.